The effects of Fusarium graminearum cell extracts and culture filtrates on the production of paclitaxel and 10-deacetylbaccatin III in suspension cell cultures of Taxus baccata L. - Arman Kamali Dehghan; Meisam Zargar; Mahsa Bamneshin; Mohtaram Mahmoudieh; Naser Safaie; Jun-Li Yang; Mohammad Reza Naghavi (BMC Plant Biology)
Abstract Background The genus Taxus (yew) is the sole producer of the paclitaxel with anticancer properties. The rising demand for plant-derived medicines has led to the overexploitation of various species and ecosystem degradation, which is further worsened by climate change. Taxus baccata L. cell culture represents a promising commercial approach for the production of taxanes. A variety of elicitors and signaling molecules have been utilized to enhance production taxanes with results significantly affected by several factors, including the specificity of the stimulant, its concentration, the timing of inoculation, and the duration of treatment. To date, no studies have revealed that the elicitors derived from Fusarium graminearum enhance 10-deacetylbaccatin III (10-DABIII) and paclitaxel production in T. baccata suspension cell cultures. Added to that, we evaluated the impact of these fungal elicitors on cell viability, growth, phenylalanine ammonia-lyase (PAL) activity, and the production levels of paclitaxel and 10-DABIII. Results We investigated the effects of autoclaved cell extracts (ACE) and autoclaved culture filtrates (ACF) derived from F. graminearum on the suspension cell cultures of T. baccata. Our results indicated that the highest paclitaxel production, 9.438 µg/g dry weight, was achieved with a 10% autoclaved culture filtrate treatment. Furthermore, the autoclaved cell extracts significantly enhanced the levels of 10-DABIII, resulting in a remarkable 7.38-fold increase at a 5% concentration compared to the control on day 21. Treatment of the cell cultures of T. baccata with ACE and ACF decreased cell viability by 31% and 23%, respectively, compared to an 18% reduction observed in the control group after 21 days. The fungal elicitors initially induced the activity of PAL in the cell cultures, followed by a subsequent decline in this enzymatic activity. Conclusions Our study offers valuable insights for biotechnological applications in pharmaceutical and agricultural industries. Moreover, this research contributes to a better understanding of elicitor-mediated improvements in paclitaxel biosynthesis, paving the way for sustainable and efficient production in T. baccata cell cultures.